IMPORTANCE OF SKIN MOISTURE IN SKIN HEALTH WSR TO BHRA-JAK PITTA - Kumar Kamal; Vyas Mahesh K.; Baghel A.S.; Patel Devang; Ghodela Naresh (International Journal of Applied Ayurved Research, 2017)
Skin is the largest organ in the body and requires regular attention to keep it healthy, young, wrinkles &blemish free. Our skin is exposed to direct sunrays along with dust, dirt and many other harmful particles present in external environment. These all affects the real health of skin in many ways but if we think about its maintenance than we certainly concentrate on its moisture level. This moisture level actually governs its protection barrier. If the skin’s moisture level be-come disrupt along with its protective barrier than skin becomes prone to the disease condition. This skin health also affected with age. The skin becomes drier so needs special care and atten-tion at this time. Here moisturizing of skin at right time plays an important role to enjoy healthy skin. It is very essential to keep skin well moisturized that help to prevent its protective level in-tact and safe so that skin remains healthy. But, unfortunately, many people do not realize the im-portance of moisturizing their skin daily which in turn produces their compromised skin health state. The different moisturizers used to maintain its protective barrier to correct the moisture level of skin but one must understand that every available moisturizer does not effectively suits for every skin type so according to particular skin type one must have to select his peculiar skin moisturizer in different seasons. According to Ayurveda, the Bhrajak Pitta is the factor which assimilates the external applications like moisturizers, sunscreen etc. in the form of lepa, abhy-anga etc. to keep its protective barrier safe and effective. It is responsible for lustre and complex-ion of the skin.